Elite golfers' kinematic sequence in full-swing and partial-swing shots - Tinmark, F.; Hellström, J.; Halvorsen, K.; Thorstensson, A. (Sports Biomechanics, 2010)
The aim of this study was to investigate whether kinematic proximal-to-distal sequencing (PDS) and speed-summation are common characteristics of both partial and full-swing shots in golf players of different skill levels and genders. A total of 45 golfers participated, 11 male tournament professionals, 21 male and 13 female elite amateurs. They performed partial shots with a wedge to targets at three submaximal distances, 40, 55 and 70 m, and full-swing shots with a 5 iron and a driver for maximal distance. Pelvis, upper torso and hand movements were recorded in 3D with an electromagnetic tracking system (Polhemus Liberty) at 240 Hz and the magnitude of the resultant angular velocity vector of each segment was computed. The results showed a significant proximal-to-distal temporal relationship and a concomitant successive increase in maximum (peak) segment angular speed in every shot condition for both genders and levels of expertise. A proximal-to-distal utilization of interaction torques is indicated. Using a common PDS movement strategy in partial and full-swing golf shots appears beneficial from mechanical and control points of view and could serve the purpose of providing both high speed and accuracy.